Eradication of Repeated Episodes of Coagulase-Negative Staphylococcus Peritonitis: A Multipronged Approach. Issue 6 (November 2019) - Haivas, Claudia-Denise; Teitelbaum, Isaac
Bacterial peritonitis continues to be a significant cause of morbidity and mortality in patients undergoing peritoneal dialysis. Episodes of peritonitis due to coagulase-negative staphylococci (CNS) are especially prone to relapse or repeat, often culminating in catheter removal and technique failure. This pattern is thought to be associated with the production of a biofilm that offers protection against antimicrobials and the host defense systems. We report the successful eradication of repeated episodes of CNS peritonitis using an aggressive multipronged therapeutic approach combining several antibiotics and a thrombolytic agent.